E-book Creator AI Drama Text Based on Role-Playing Model in Learning Speaking Skills for High-Grade Learners - Avril Salmania Ananda Putri; Panca Dewi Purwati (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Many fifth-grade elementary school students lack self-confidence in speaking skills, especially in the topic of drama texts. This affects their speaking skills, which tend to be low. The purpose of this study is to develop an AI-based Drama Text E-book Creator with a Role-Playing Model for teaching speaking skills to fifth-grade elementary school students. The method used in this research is Research and Development (R&D) with the Borg and Gall model. The subjects of this study are subject matter experts and media experts. The product trial involves teachers and 13 fifth-grade students. The sample used in the research for the small-scale trial consists of 6 students. The data collection methods are observation, interviews, questionnaires, and documentation. The instruments used for data collection are questionnaires and assessment sheets. The data analysis techniques used are qualitative and quantitative descriptive analysis. The results of the study show that the feasibility validation from the media expert is 93.75% with an average score of 3.75 (Very Feasible). The feasibility validation from the subject matter expert is 90.52% with an average score of 3.62 (Very Feasible). The effectiveness test shows that the pretest score for the small-scale trial is 65.08 (Not Mastered), and the posttest score is 85.47 (Mastered). The effectiveness test results show an improvement of 20.38%. It can be concluded that based on the feasibility and effectiveness tests, the E-book Creator media is deemed feasible to be used in learning.